Builders and planners a history of land-use and infrastructure planning in the Netherlands - Arts, Jos 1967- (Eburon Academic Publishers, 2016)
This book looks at the intersection of Dutch infrastructure builders and Dutch spatial planners, both of whom have historically desired to order Dutch space. From the professionalization of builders and planners in the 1920s, when they first sought to leave their mark on the design of the land, to the subsequent transition from urban to regional and national spatial planning, and the groups’ increasingly public roles in the 1950s and ’60s, Builders and Planners is a story of collaboration and conflict, of coalitions and opposition between two expert groups working in the Dutch space. Also including case studies of particular construction projects that shed light on the difficult path from plan to completion, as well as offering insight into the unique nature of planning in the Netherlands through detailed comparison with Belgium, Builders and Planners provides new and fascinating perspectives on the history of Dutch planning and planners.
Literaturverzeichnis: Seite 471-498
Keywords: Geschichte 1950-2016; Stadtplanung; Städtebau; Niederlande